Integrated control of wood destroying basidiomycetes combining Cu-based wood preservatives and Trichoderma spp. - Ribera, Javier; Fink, Siegfried; Bas, Maria del Carmen; Schwarze, Francis W. M. R. (PLOS ONE, 2017)
The production of new generation of wood preservatives (without addition of a co-biocide) in combination with an exchange of wood poles on identical sites with high fungal inoculum, has resulted in an increase of premature failures of wood utility poles in the last decades. Wood destroying basidiomycetes inhabiting sites where poles have been installed, have developed resistance against wood preservatives. The objective of the in vitro studies was to identify a Trichoderma spp. with a highly antagonistic potential against wood destroying basidiomycetes that is capable of colonizing Cu-rich environments. For this purpose, the activity of five Trichoderma spp. on Cu-rich medium was evaluated according to its growth and sporulation rates. The influence of the selected Trichoderma spp. on wood colonization and degradation by five wood destroying basidiomycetes was quantitatively analyzed by means of dry weight loss of wood specimens. Furthermore, the preventative effect of the selected Trichoderma spp. in combination with four Cu-based preservatives was also examined by mass loss and histological changes in the wood specimens. Trichoderma harzianum (T-720) was considered the biocontrol agent with higher antagonistic potential to colonize Cu-rich environments (up to 0.1% CuSO4 amended medium). T. harzianum demonstrated significant preventative effect on wood specimens against four wood destroying basidiomycetes. The combined effect of T. harzianum and Cu-based wood preservatives demonstrated that after 9 months incubation with two wood destroying basidiomycetes, wood specimens treated with 3.8 kg m-3 copper-chromium had weight losses between 55–65%, whereas containers previously treated with T. harzianum had significantly lower weight losses (0–25%). Histological studies on one of the wood destroying basidiomycetes revealed typical decomposition of wood cells by brown-rot fungi in Cu-impregnated samples, that were notably absent in wood specimens previously exposed to T. harzianum. It is concluded that carefully selected Trichoderma isolates can be used for integrated wood protection against a range of wood destroying basidiomycetes and may have potential for integrated wood protection in the field.